Wheat Growing and Changing Farming Systems in South African Dryland Margins: The Case of the Sneeuberg, South Africa. (2nd June 2016) - Suich, Helen; Boardman, John
Abstract: The contribution of stock keeping to land degradation in the Karoo has been extensively studied, but other causes have been rarely examined. The paper uses a combination of key informant interviews and a review of published and unpublished documentary sources to describe the history of wheat growing in the Sneeuberg area of the Karoo since European settlement, until the 1970s when annual crop cultivation collapsed. Early cultivation was primarily for subsistence purposes, although the development of infrastructure and growth in markets in the 19th century encouraged commercial crop production. Some farmers continued growing wheat partly to sustain the tradition into the mid‐20th century, although by that time, most growers relied on the wheat as a winter stockfeed. Several factors were found to have contributed to the collapse, with land degradation only rarely playing a part in contemporary decisions to stop wheat farming. Far more important were the comparative advantages of other stockfeeds such as lucerne, changes in state regulations governing crops and prices, and the perceptions of farmers regarding changes in rainfall patterns. Copyright © 2016 John Wiley & Sons, Ltd.